2011
DOI: 10.1590/s1517-83822011000200020
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological monitoring mf mineral water commercialized in Brazil

Abstract: The quality of mineral water commercialized in Brazil regarding the microbial content was analyzed and the results were compared with the standards established by the current legislation. Results demonstrated there was no bacterial contamination, but several types of fungi were found. Therefore, bottled mineral water could be considered a possible route for the transmission of filamentous fungi and yeasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
13

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 15 publications
2
7
0
13
Order By: Relevance
“…Also, for this group of microorganism was not observed constancy which reinforces the suspicion that the package might be responsible for this kind of contamination. Pontara et al (2011) also verified lower yeast incidence when in 15 samples there were observed 32 colonies related to fungi, being 22 molds and only 10 yeasts.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Also, for this group of microorganism was not observed constancy which reinforces the suspicion that the package might be responsible for this kind of contamination. Pontara et al (2011) also verified lower yeast incidence when in 15 samples there were observed 32 colonies related to fungi, being 22 molds and only 10 yeasts.…”
Section: Discussionsupporting
confidence: 60%
“…In the fungi research in the water, there was observed the presence of 333 samples, which 218 of them, were confirmed as filamentous fungi (Oliveira, 2010). Other authors also identified fungi in water samples and among them, pathogenic species and toxin producers, suggesting harm for the health, mainly to children, elderly and patients with impaired immunologic system (Yamaguchi et al, 2007;Nunzio & Yamaguchi, 2010;Oliveira, 2010;Nunes & Fuzihara, 2011;Pontara et al, 2011). The presence of fungi in water was also referred by another author, who suggested being, the microorganisms, the responsible for sensorial alterations in the water, such as color and odor (Gonçalves et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean prevalence of P. aeruginosa in local bottled water brands was 8.6% while for imported brands it was 0 .6% with the prevalence in different brands illustrated in Figure 1. Since standards require zero prevalence for P. aeruginosa, higher prevalence in local brands may suggest that there is non-compliance with good manufacturing practices as reported in other studies (Abd El-Salam et al, 2008;Nunes Filho et al, 2008;Pontara et al, 2011;Raj, 2005). In a study conducted in Bulawayo in 2002, P. aeruginosa was found to have 6.7% prevalence (Okagbue et al, 2002).…”
Section: Resultsmentioning
confidence: 88%